Psychomotor Agitation Non-responsive to Treatment: A Case Report of Phenibut Withdrawal Syndrome - Esposito, Cecilia Maria; Mandolini, Gian Mario; Delvecchio, Giuseppe; Fiorentini, Alessio; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
Background and Objectives Phenibut (4-Amino-3-Phenyl-Butyric Acid), acting as a GABA-B receptor agonist, has a beneficial effect on anxiety. Although its medical use is not approved in Western countries, it can be easily obtained worldwide via the Internet, so it spread as a substance of abuse. In recent years, some case reports have therefore highlighted episodes of acute toxicity or withdrawal, but it is still a largely unknown phenomenon. Methods In this case report, a 50-year-old woman was admitted to the emergency room with psychomotor agitation, psychotic symptoms and insomnia, and was non-responsive to treatment. She was hospitalized at the psychiatry ward for twenty-five days and gave her consent for the publication of the present case report. Results The suspicion of phenibut withdrawal made it possible to establish the appropriate management, leading to the restitutio ad integrum of the psychopathological case. Conclusions In the face of an incoercible psychomotor agitation case, knowledge of the so-called Novel psychoactive substance and the clinical frameworks of intoxication and withdrawal that this entail allows for more appropriate clinical management. This is a scientifically significant report as it provides therapeutic and outcome data as regards a syndrome that is still quite unfamiliar.